Conserved Genoarchitecture of the Basal Hypothalamus in Zebrafish Embryos - Schredelseker, Theresa; Driever, Wolfgang (Frontiers in Neuroanatomy, 2020)
Analyses of genoarchitecture recently stimulated substantial revisions of anatomical models for the developing hypothalamus in mammalian and other vertebrate systems. The prosomeric model proposes the hypothalamus to be derived from the secondary prosencephalon, and to consist of alar and basal regions. The basal hypothalamus can further be subdivided into tuberal and mamillary regions, each with distinct subregions. Albeit being a widely used model system for neurodevelopmental studies, no detailed genoarchitectural maps exist for the zebrafish (Danio rerio) hypothalamus. Here, we compare expression domains of zebrafish genes, including arxa, shha, otpa, isl1, lhx5, nkx2.1, nkx2.2a, pax6, and dlx5a, the orthologs of which delimit specific subregions within the murine basal hypothalamus. We develop the highly conserved brain-specific homeobox (bsx) gene as a novel marker for genoarchitectural analysis of hypothalamic regions. Our comparison of gene expression patterns reveals that the genoarchitecture of the basal hypothalamus in zebrafish embryos 48 hours post fertilization is highly similar to mouse embryos at E13.5. We found the tuberal hypothalamus in zebrafish embryos to be relatively large and to comprise previously ill-defined regions around the posterior hypothalamic recess. The mamillary hypothalamus is smaller and concentrates to rather medial areas in proximity to the anterior end of the neural tube floor plate. Within the basal hypothalamus we identified longitudinal and transverse tuberal and mamillary subregions topologically equivalent to those previously described in other vertebrates. However, the hypothalamic diencephalic boundary region and the posterior tuberculum still provide a challenge. We applied the updated prosomeric model to the developing zebrafish hypothalamus to facilitate cross-species comparisons. Accordingly, we applied the mammalian nomenclature of hypothalamic organization to zebrafish and propose it to replace some controversial previous nomenclature.